(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The most common cause of disability in children with musculoskeletal disorders are dysplastic hip instability disorders, which include: hip dysplasia, congenital subluxation, and congenital and pathological hip dislocation.